Verification of placental growth factor and soluble-fms-like tyrosine kinase 1 assay performance in late pregnancy and their diagnostic test accuracy in women with reduced fetal movement. (May 2020) - Armstrong-Buisseret, Lindsay K; Haslam, Shonagh; James, Tim; Bradshaw, Lucy; Heazell, Alexander EP
Background: Placental growth factor (PlGF) and soluble-fms-like tyrosine kinase 1 (sFlt-1) are biomarkers of placental function used to aid the diagnosis and prediction of pregnancy complications. This work verified the analytical performance of both biomarkers and provides preliminary diagnostic accuracy data to identify adverse pregnancy outcome in women with reduced fetal movement. Methods: Verification of sFlt-1 and PlGF assays included a comparative accuracy assessment of 24 serum samples analysed at six different sites and laboratory-specific precision estimates. The sFlt-1/PlGF ratio was assessed in serum samples obtained prospectively from 295 women with reduced fetal movement ≥36 weeks' gestation; diagnostic accuracy was evaluated using 2 × 2 tables and area under the receiver operator characteristic (AUROC) curve. Results: Regression analysis showed that performance between sites was good with Passing-Bablok slopes ranging from 0.96 to 1.05 (sFlt-1) and 0.93 to 1.08 (PlGF). All sites had a mean bias <15%, although there was poorer agreement at the lowest PlGF concentrations. All within- and between-batch coefficients of variation were <10%. In 289 women with an appropriately grown fetus, an sFlt-1/PlGF ratio ≥38 had a sensitivity of 0.20 (95% confidence interval [CI] 0.07, 0.41), specificity of 0.88 (95% CI 0.83, 0.92) and AUROC curve of 0.58 (95% CI 0.47, 0.68) to identify adverse pregnancy outcome. Conclusions: Analytical performance of the sFlt-1 and PlGF assays was comparable across different sites. The sensitivity of sFlt-1/PlGF to identify adverse pregnancy outcome in women with reduced fetal movement was considered acceptable, in the absence of other tests, to progress to a pilot randomized controlled trial.